2019
DOI: 10.1088/1742-6596/1279/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Estimating snow cover area in south of Turkey using the Normalized Difference Snow Index (NDSI) form MODIS Satellite Images

Abstract: Snow and Ice–cover area information is important for a wide variety of scientific climate studies, water source and management applications. The NASA Earth Observing System (EOS) Moderate Resolution Imaging Spectroradiometer (MODIS) satellite, provides improved capabilities to observe snow-ice coverarea from space and has been successfully using a Normalized Difference Snow Index (NDSI) methodes, This technique is the same procedure for the Normalized Difference Vegetation Index (NDVI), along with threshold te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A study was conducted to detect the snow cover in the regions of northern Iraq (Sulaymaniyah), western Iran (Kermanshah), and parts of Turkey, where the NDSI algorithm gave good results in separating the snow cover from clouds and other features, based on a study of [14]One researcher examine whether partial snow cover estimates can be improved to estimate snow area for headwaters of the Tigris and Euphrates rivers. The results showed that climate change has a negative impact on the Middle East region and there is a change in the amounts of snowfall in southern Turkey and northern Iraq, in the first three months of the year, between 2014 and 2016 [15]. Found out that the threshold value of NDSI > 0.4 was used to indicate snow coverage in Seyhan city in the Eastern Mediterranean region of Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted to detect the snow cover in the regions of northern Iraq (Sulaymaniyah), western Iran (Kermanshah), and parts of Turkey, where the NDSI algorithm gave good results in separating the snow cover from clouds and other features, based on a study of [14]One researcher examine whether partial snow cover estimates can be improved to estimate snow area for headwaters of the Tigris and Euphrates rivers. The results showed that climate change has a negative impact on the Middle East region and there is a change in the amounts of snowfall in southern Turkey and northern Iraq, in the first three months of the year, between 2014 and 2016 [15]. Found out that the threshold value of NDSI > 0.4 was used to indicate snow coverage in Seyhan city in the Eastern Mediterranean region of Turkey.…”
Section: Introductionmentioning
confidence: 99%